Urgensi Pembelajaran Perkalian Bilangan Dengan Pendekatan Matematika Realistik Indonesia Pada Siswa Tunarungu - Wahyudi Hartono, ; Novita Nur Samiadi, (Pendidikan Luar Biasa, 2008)
In this research has purpose to prove whether the Indonesia Realistic Mathematic Approach can increase mathematic achievement the student with hearing impairment. Besides, it investigated  whether it appropriates to be given for student with hearing impairment. On practicing this research used randomized control group pretest posttest design. That divided the second elementary student in two groups, is a experiment group with multiplication learning by realistic approach and  a control group with memorizing multiplication learning. The result in this research would be analyzed with Mann Whitney test formula. And used questionnaire to seeing student response toward this approach.The result by Mann Whitney test formula was U = 1,5, mean = 10, deviation standard = 4,08 an standard value = -2,08 it mean reached  Ho decide  there is no effect from realistic mathematic approach learning toward achievement mathematic of Karya Mulia student is denied. And than the result from questionnaire seeing student response toward realistic approach was 80% student in experiment groups has stated like learn mathematic with realistic approach, And 75% student in control groups was not like learn mathematic.